2019
DOI: 10.1016/j.jbiomech.2019.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of joint torque inputs during an induced speed analysis of a swinging motion

Abstract: This study proposed a method to quantify direct and indirect effects of the joint torque inputs in the speed-generating mechanism of a swinging motion. Linear and angular accelerations of all segments within a multi-linked system can be expressed as the sum of contributions from a joint torque term, gravitational force term and motion-dependent term (MDT), where the MDT is a nonlinear term consisting of centrifugal force, Coriolis force and a gyroscopic effect moment. Direct effects result from angular acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The racket model (two rigid segments connected by a virtual joint) is a simplification of the dynamic behaviour of a racket, which adopts an infinite number of mode shapes under loading; however, the current approach has been used previously to measure racket kinematics [15]. Future work should also aim to understand the direct vs. indirect effects of the torques within the smash with respect to the generation of speed [28], i.e., whether the high speeds generated are a result of instantaneous torques produced by the musculature at the joint or developed by cumulative torques from prior torques at other joints. The 'resultant moments' approach used in this study does not allow a distinction between muscular, gravitational and velocity-dependent torques and therefore specific recommendations for strengthening specific muscle groups should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The racket model (two rigid segments connected by a virtual joint) is a simplification of the dynamic behaviour of a racket, which adopts an infinite number of mode shapes under loading; however, the current approach has been used previously to measure racket kinematics [15]. Future work should also aim to understand the direct vs. indirect effects of the torques within the smash with respect to the generation of speed [28], i.e., whether the high speeds generated are a result of instantaneous torques produced by the musculature at the joint or developed by cumulative torques from prior torques at other joints. The 'resultant moments' approach used in this study does not allow a distinction between muscular, gravitational and velocity-dependent torques and therefore specific recommendations for strengthening specific muscle groups should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The rigid link model and the locations of the IMUs attached to the segments are shown in Figure 1a,b. Anatomical constraint axes (e.g., varus/valgus axis at the elbow joint; internal/external rotation axis at the wrist joint), along which the joints could not rotate freely, were considered [6]. Since the ball was assumed to be fixed to the hand segment coordinate system during the pitching motion, the hand and ball were assumed to be one rigid segment in this study.…”
Section: Dynamical Model Of Upper Limb Segments With a Ballmentioning
confidence: 99%
“…Koike proposed an equation of motion consisting of a joint torque term, a gravitational term, and a motion-dependent term consisting of centrifugal forces and Coriolis forces. It was shown that the contribution of each term greatly differs depending on which exercise is focused (Koike et al, 2019).…”
Section: Introductionmentioning
confidence: 99%